Pottery use across the Neolithic transition in northern Belgium: evidence from isotopic, molecular and microscopic analysis - Dimitri Teetaert; Marieke Vannoorenberghe; Thomas Van de Velde; Mathieu Boudin; Samuel Bodé; Lucy Kubiak-Martens; Mathijs Baert; Frederic Lynen; Philippe Crombé; Pascal Boeckx (Archaeological and Anthropological Sciences, 2024)
This study represents the first extensive residue analysis of prehistoric pottery from northern Belgium. It examines pottery use and culinary practices across the Mesolithic-Neolithic transition, from the late 6th to the early 4th millennium cal BC. Residue analyses were performed on more than 200 samples from nine archaeological sites, representing different cultural groups from this transitional phase. This includes the analysis of charred food residues encrusted on the vessel surfaces by elemental analysis-isotope ratio mass spectrometry (EA-IRMS), gas chromatography-mass spectrometry (GC-MS), stereomicroscopic analysis and Scanning Electron Microscopy (SEM), as well as the analysis of absorbed lipids by gas chromatography-combustion-isotope ratio mass spectrometry (GC-C-IRMS). This study provides the first evidence of ruminant dairy fats in Early Neolithic Limburg pottery, supporting the hypothesis that this pottery was produced and used by LBK farmers rather than hunter-gatherer populations. The first indigenous pottery of the Swifterbant culture was frequently used to process freshwater fish (often together with plant foods) and ruminant meat, although several of the studied vessels likely contained mixtures of resources which could also include porcine products. Ruminant dairy is nearly absent from this pottery. Similar results were obtained for pottery of the subsequent Michelsberg culture/Group of Spiere of the late 5th and early 4th millennium cal BC. The limited presence of ruminant dairy fats in this pottery contrasts with the findings for Middle Neolithic pottery from neighbouring regions, providing further evidence for the existence of regional variations in pottery use or culinary practices throughout prehistoric NW Europe. However, our current view of pottery use during the Mesolithic-Neolithic transition in northern Belgium might be biased by the difficulties in distinguishing between wild and domesticated ruminant adipose fats as well as in detecting plant foods through lipid residue analysis.